Fibre links for the WEAVE instrument: the making of - Mignot, S; Bonifacio, P; Fasola, G; Dalton, G; Lewis, I (Society of Photo-optical Instrumentation Engineers, 2020)
The WEAVE instrument nearing completion for the William Herschel Telescope is a fiber-fed spectrograph operating in three different modes. Two comprise deployable fibers at the prime focus for point-like objects and small integral field units (IFU), the third is a large IFU placed at the center of the field. Three distinct fiber systems support these modes and route the photons to the spectrograph located on the Nasmyth platform 33m away: the first features 960+940 fibers and is duplicated to allow configuring the fibers on one plate while observation is carried out on the other, the second has 20 hexagonal IFUs featuring 37 fibers each, the third is a large array of 609 fibers with twice the former’s diameter. The large number of fibers and the diversity of their instantiation have made procurement of the parts and assembly of the custom cables a challenge. They involve project partners in France, the UK and the Netherlands and industrial partners in France, Canada, the USA and China to combine know-how and compress the schedule by parallelizing assembly of the cables. Besides the complex management that this induces, it has called for revising the fibers’ handling to relax tolerances and for a rigorous assessment of the conformity of the products. This paper tells the story of the making of the fiber links, presents the overall organization of the procurement and assembly chains together with the inspection and testing allowing for assessing the conformance of the hardware delivered.